2005
DOI: 10.1097/01.ju.0000154565.37397.4d
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Penile Carcinoma Benefit From Immediate Resection of Clinically Occult Lymph Node Metastases

Abstract: Early resection of lymph node metastases in patients with penile carcinoma improves survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
158
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(170 citation statements)
references
References 18 publications
6
158
0
6
Order By: Relevance
“…Identifying patients with occult metastases is important because it has been shown that immediate lymphadenectomy confers a survival advantage over surgery deferred until palpable disease develops (47,48). In a recent series of forty patients, the 3-year disease-specific survival of patients with metastatic nodes detected on surveillance was 35% versus 84% in those who underwent early resection (48). These numbers are very similar to those that have been reported with more extensive (6-7 year) follow-up (47).…”
Section: Assessment Of the Inguinal Nodessupporting
confidence: 69%
See 1 more Smart Citation
“…Identifying patients with occult metastases is important because it has been shown that immediate lymphadenectomy confers a survival advantage over surgery deferred until palpable disease develops (47,48). In a recent series of forty patients, the 3-year disease-specific survival of patients with metastatic nodes detected on surveillance was 35% versus 84% in those who underwent early resection (48). These numbers are very similar to those that have been reported with more extensive (6-7 year) follow-up (47).…”
Section: Assessment Of the Inguinal Nodessupporting
confidence: 69%
“…The staging modalities previously mentioned offer hope that this subgroup may be identified in a non-invasive manner in the near future. Identifying patients with occult metastases is important because it has been shown that immediate lymphadenectomy confers a survival advantage over surgery deferred until palpable disease develops (47,48). In a recent series of forty patients, the 3-year disease-specific survival of patients with metastatic nodes detected on surveillance was 35% versus 84% in those who underwent early resection (48).…”
Section: Assessment Of the Inguinal Nodesmentioning
confidence: 99%
“…Different treatments were performed in similar clinical settings. These facts reflect the lack of standardization of the treatment of penile cancer nowadays, particularly in relation to lymph node involvement (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…This apparent improvement in survival is in keeping with the reported benefits of early node surgery in high-risk cases. 2,3 The Improving Outcomes Guidance states that penis cancer should be treated in a supraregional centre serving a population of at least 4 million and treating 25 or more cases per year. Our referral population reached 3.1 million in 2005 and, at that time, we were referred an average of 20 patients annually.…”
Section: Discussionmentioning
confidence: 99%